Desenvolvimento de fixadores com efeito memória de forma para união de chapas metálicas - Paz, Josivan Silva da (2017)
The shape memory alloys belong to a class of metal materials capable of recovering pseudoplastic deformation when subjected to appropriate thermomechanical treatments. This recovery of pseudoplastic deformation allows the use of these alloys in various industrial applications, such as fastening elements. This work had as main objective the development of fasteners with shape memory, made from the alloy Cu-11,8Al-0,58Be-0,5Nb0,27Ni for joining metallic plates. The alloy was obtained by conventional casting, heat treated and characterized by optical microscopy. The fasteners were made by turning and wire EDM process. The mechanical characterization was performed by shear and pullout tests. Three types of repairers were made in this work, which were called: T type, Y type and self-locking head. The fixation of the plates was obtained through the functional properties presented by the alloy under study – the shape memory alloy (Y-type and self-locking head) and superelasticity (T type). After the tear-off tests, the T-type fastener had the highest maximum load value in comparison with the other fasteners, including the commercial rivet also used for comparison. For the joint shear tests, the Y-type fastener presented the highest load. In view of the results obtained, it is possible to say that shape memory fasteners are presented as a viable alternative for use as metal sheet fastening devices, especially in situations where conventional riveting becomes impractical or impracticable for various reasons.